Energy expenditure and muscle activity in active and passive commute among elderly - Kuula, Anna-Stina (2011)
Since the amount of elderly people and people being overweight are increasing, there should be means to prevent people from getting weight and to ensure longer independency and ability in everyday living among elderly people to decrease the costs that are caused by these trends.